2022
DOI: 10.1186/s12879-022-07872-8
|View full text |Cite|
|
Sign up to set email alerts
|

Human brucellosis and fever of unknown origin

Abstract: Background Human brucellosis has become one of the major public health problems in China, and increases atypical manifestations, such as fever of unknown origin (FUO), and misdiagnosis rates has complicated the diagnosis of brucellosis. To date, no relevant study on the relationship between brucellosis and FUO has been conducted. Methods We retrospectively reviewed the medical charts of 35 patients with confirmed human brucellosis and prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“… 3 Treatment is often delayed because of misdiagnosis. 5 There are approximately half a million new infections reported worldwide each year, 6 with a large number of livestock infections, which has a large economic impact. A main route of Brucella infection in the respiratory system is aerosol transmission, 7 , 8 and subsequent blood transmission may be the most important route of lung infection.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Treatment is often delayed because of misdiagnosis. 5 There are approximately half a million new infections reported worldwide each year, 6 with a large number of livestock infections, which has a large economic impact. A main route of Brucella infection in the respiratory system is aerosol transmission, 7 , 8 and subsequent blood transmission may be the most important route of lung infection.…”
Section: Discussionmentioning
confidence: 99%
“…Other symptoms and signs are abdominal pain, splenomegaly, and hepatomegaly [54]. Apart from all the aforementioned symptoms, brucellosis should also be considered in the differential diagnosis of a fever of unknown origin, especially in non-endemic areas [55]. Complicated forms of the disease include osteoarticular, genitourinary, neurologic, cardiovascular, and pulmonary involvement [56,57].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Human-to-human transmission takes place through blood transfusion, bone marrow transplantation, and mother-to-fetus transmission ( 3 ). The signs and symptoms of brucellosis are not specific, fever, sweat, fatigue, and joint ache are the most common manifestation of human brucellosis, these are similar to influenza, severe colds, coronavirus disease 2019 (COVID-19), malaria, and other infectious diseases, so clinical diagnosis is difficult in place of lack of health facility and specific and rapid diagnostic methods ( 4 , 5 ). An epidemiological survey based on 2060 cases collected from brucellosis clinics in China showed that 57.62% of patients were misdiagnosed or suspected of having other diseases with similar clinical symptoms ( 6 ).…”
Section: Introductionmentioning
confidence: 99%